FRI0620-HPR THE EFFECT OF THERMOFORMABLE FOOT ORTHOSES ON WALKING IN RHEUMATOID ARTHRITIS PATIENTS: PRELIMINARY RESULTS FROM AN OPEN CLINICAL TRIAL. (13th June 2020) - Fellous, S.; Rkain, H.; Ilham, A.; Benzakour, L.; Latifa, T.; Alami, N.; Guieu, R.; Jammes, Y.; Hajjaj-Hassouni, N.; Allali, F.
Abstract : Background: Foot pain is common in rheumatoid arthritis and appears to persist despite modern day medical management. Objectives: To evaluate the impact of thermoformable foot orthoses on walking in rheumatoid arthritis (RA) patients. Methods: This is a open clinical trial, that included 14 consecutive patients (85, 7% female, mean age 54, 8 ± 10 years) with RA (median duration of progression of 9 [5-12] years), the average DAS28 was 2, 7+/-1, 2 and the functional impact objectified by the Health Assessment Questionnaire (HAQ) was on average 0.9 ± 0.7. The foot problem was bilateral in 100% and inaugural in 85.7% of the cases. The 14 rheumatoid subjects were examined and appropriate foot orthoses were prescribed according to each patient's needs. All the patients were evaluated at baseline and 8 weeks after use of orthoses. Gait pain, difficulty walking and the 10 Meter Walk test were noted at each appointment. We used dynamic baropodometric analysis to assess postural evaluation. We calculated the lateral-medial index of each foot before and after the use of orthoses. Results: A significant decrease in walking pain (p = 0.002) and difficulty walking (p = 0.02) was found with the use of orthoses. The variations in 10 meter walk test and dynamic baropodometric parameters were not significant (p>0, 05). There were no significant correlations between pain and difficulty walking, the progression of RA, the duration of foot damage and the functional impact measured by the HAQ. Conclusion: Thermoformable foot orthoses significantly reduced pain and difficulty walking. The absence of factors associated with pain and difficulty walking could possibly be related to the small sample size. Disclosure of Interests: None declared